PREPARATION AND EVALUATION OF METOLAZONE SOLID DISPERSIONS AND FAST DISSOLVING TABLETS USING STERCULIA FOETIDA SEED STARCH AND PLASDONE K-29/32 AS SUPERDISINTEGRANTS - DOPPALAPUDI, SANDEEP; SURYADEVARA, VIDYADHARA (International Journal of Applied Pharmaceutics, 2020)
Objective: The objective of the current study is to improve the solubility of the Biopharmaceutical Classification System (BCS) Class-II drug, Metolazone, using various superdisintegrants. Methods: Starches were extracted from Sterculia foetida seed powder by water and alkali techniques i.e., sodium hydroxide at 0.1%, 0.25% and 0.5% concentrations. Several phytochemical and physicochemical parameters were evaluated on the extracted starches. Solid dispersions of Metolazone were prepared by the solvent evaporation technique using plasdone K-29/32 alone and by mixing plasdone K-29/32 with Sterculia foetida seed starch. Various physical parameters were evaluated for the prepared solid dispersions. Tablets were prepared using Metolazone solid dispersions and varying concentrations of Sterculia foetida seed starch by direct compression technique. Pre and post-compression parameters were evaluated along with in vitro drug release studies, characterization using Scanning Electron Microscopy (SEM) and stability studies. Results: Phytochemical tests showed the presence of starch in all extracts. Starch prepared from 0.1% sodium hydroxide (SFS2) showed best physicochemical properties. In vitro dissolution studies revealed that solid dispersion MS4 containing Metolazone and plasdone K-29/32 in 1:3 ratios showed better drug release. Formulation MPT6 containing MS5 solid dispersion with 15% w/w of SFS2 showed enhanced drug release. SEM studies revealed no major interactions between drugs and excipients. Accelerated stability studies showed that all tablets were stable. Conclusion: Sterculia foetida seed starch and plasdone K-29/32 have enhanced the solubility of Metolazone.